Thermal and energy performance for different configuration of insulation on building envelope in tropical climates / Noor Hafizah Abdul Halim - Abdul Halim, Noor Hafizah (2016)
This research investigates the performance of thermal insulation for air-conditioning buildings in the tropical climate of Malaysia. These studies were performed via field data measurements and simulation using two identical test building located in Universiti Teknologi MARA, Shah Alam, Selangor campus. The performances were appraised by the thermal impact and energy consumption of air-conditioning system for three cooling modes. The three cooling modes are 24-hours, office-hours (daytime) and residential-hours cooling (nighttime) which are represents the occupied period in the building types. A Field data measurement was performed using real external condition while simulation study was performed using Model Year Climate data of Subang, Malaysia. Results show that the installation of thermal insulation to improve the thermo physical properties of building envelope in roof, ceiling and wall have the significant impact in thermal and energy performances. The use of computer simulation of Integrated Environmental Solution was first validated to ensure the acceptable output from the simulation before to further the investigation. From the field study, it was found that the roof and ceiling insulation most significant for the daytime cooling when saving the energy up to 0.56 % and 13.24 % respectively. Meanwhile, for each cooling scenarios, ceiling insulation was most significant compared to the roof insulation when saving the energy up to 4.20 %, 0.53 %, and 2.47 % for 24-hours, office-hours and residential-hours cooling scenarios respectively. The performance also considers the ability of thermal insulation to reduce the attic and indoor temperature. Further investigation using simulation studies to investigate the optimum configuration of thermal insulation in roof, ceiling, and wall have found that insulated of roof, ceiling, and wall in one model give the highest saving for 24-hours and daytime cooling up to 53.81 % and 49.37 % respectively. For nighttime cooling, the insulated ceiling and wall only gives the highest saving of up to 40.15 %.